The Influence Electronic Word Of Mouth And Product Diversity On Online Purchase Decisions Through The Shopee Application - Andi Chandra; Taufik Bustami (Journal of Indonesian Management, 2024)
This research was conducted on Shopee users in Topos District with the problem formulation of what are the influence of Electronic Word Of Mouth and product diversity on online purchasing decisions through the Shopee application? The purpose aim of this study is to determine whether Electronic Word Of Mouth and product diversity influences the online purchase decisions through the Shopee application. The population in this study was Shopee users in Topos district, Lebong Regency, totaling 120 respondents. The sampling technique used accidental sampling Based on predetermined criteria, totaling 120 respondents. The data that has been processed were analyzed using SPSS 26 formulas. Based on the results of the research conducted on the influence of Electronic Word Of Mouth and Product Diversity on online purchase decisions through the Shopee application, it can be concluded as follows: Electronic Word Of Mouth significantly influence online purchase decisions Through the Shopee application, product diversity has a significantly influence online purchase decisions through the Shopee application, Electronic Word Of Mouth (X1 ) and Product Diversity (X2 ) simultaneously give significant influence on online purchase decisions (Y) through the Shopee application. Based on the correlation coefficient test, the value of R = 0.884 and the coefficient of determination = 0.782, have meaning that Electronic Word Of Mouth (X1 ) and Product Diversity (X2) contributes the influence by 0.782 or 66.6% on online purchase decisions (Y) Through the Shopee application, while the remaining 0.218 or 21.8% is influenced by other variables not included in this study.